Carrying out hydraulic calculation of the aquifer of pumping stations and work with sediments (in the example of the Ulugnor pumping station) (Eurasian Journal of Engineering and Technology, 2022)
In this article, further improvement of the working conditions of the water-carrying channel of the pumping station, development of irrigation and reclamation facilities. Analysis of design information, operating conditions and operation of the Ulognor pumping station, and based on this, development of scientifically based measures and recommendations for increasing the efficiency of the pumping station's operating mode